Peningkatan Literasi Digital Guru MI Plus Ja-Alhaq Kota Bengkulu Melalui Pemanfaatan Aplikasi Canva Dalam Penyusunan Bahan Ajar Kreatif - Neza Agusdianita; Debi Heryanto; Yusnia; Rizqa Dwi Shofiya Maghfira Izzania (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2026)
Madrasah Ibtidaiyah (MI) teachers are required to deliver engaging and contextual learning amid the demands of 21st-century digital literacy; however, at MI Plus Ja-AlHaq, Bengkulu City, most teachers still rely on conventional methods with text-based teaching materials that lack visual elements, resulting in student learning fatigue and low teacher digital competence in designing instructional media. This community service activity aims to improve teachers' digital literacy and creative teaching material design skills through a Canva application utilization workshop. The method applied was a structured observational and modeling approach consisting of four phases: the attention phase (administration of a pretest questionnaire to identify needs), the retention phase (delivery of material on Canva concepts, features, and visual message design principles), the reproduction phase (guided independent and group practice in developing teaching materials), and the motivation phase (appreciation, posttest evaluation, and encouragement toward classroom implementation). The results showed a significant improvement, with teachers' knowledge scores on Canva and digital literacy increasing from an average of 68 to 89, while teaching material design skill scores increased from an average of 65 to 92. This improvement indicates that the structured modeling approach effectively builds MI teachers' confidence and technical competence in utilizing visual technology for learning. The activity implies the need for sustainable replication of similar programs to support the digital transformation of education at the madrasah level.